Design of household level arsenic treatment system in Cambodia : evaluation of laterites in column adsorption study - Ekklesia, Eveline (2009)
Arsenic (As) concentration in groundwater was found significantly high in Kandal Province, Cambodia; especially Chroy Takeo Commune. Hence, the performance of Cambodian natural adsorbents, i.e. laterites, in removing As from groundwater to less than 0.05 mg/L was evaluated. Besides, the parameters needed for the design of As treatment system were also determined. Three types of laterites from three different places at the vicinity of Chroy Takeo Commune were investigated for the feasibility of As removal in column mode operation. The column studies were conducted in a 3.6 cm internal diameter column with 10 cm bed depth. Initial As(V) concentration was 0.5 mg/L. The sizes of laterites were 2-4 mm. The Phnom Penh (PP) laterite B was found to have the longest breakthrough volume compared with PP laterite A and Andoung (AD) laterite. pH, turbidity, colour, iron (Fe), aluminium (Al), and manganese (Mn) were monitored to ensure a safe drinking water quality. Overall the water quality was within the permissible limit. Further column studies were carried out by varying the flow rates. Effect of flow rate on the breakthrough volume was investigated. It was found that the slowest flow rate which gave the longest EBCT (170 min) has the longest breakthrough volume. Therefore, 170 min was chosen as the operational EBCT. This gave adsorption capacity of 0.03 mg As(V) per gram of 2-4 mm PP laterite B until 61.8 bed volumes. Using this adsorption capacity, the service time was 38 days if the 2-4 mm PP laterite B is designed with 0.3 m x 0.3 m x 0.3 m in dimensions to give the required daily household water demand of 50 L. Hence, it is concluded that the use of 2-4 mm PP laterite B is practical in that Commune. Ultimately, it is recommended that the adsorption capacity of 2-4 mm PP laterite B need to be obtained until the breakthrough point with the column operation at EBCT 170 min.